Algorithm for Mesh Adaptation to a Flow Field with a Bow Shock Wave - Voronich, I. V.; Smirnova, N. S.; Titarev, V. A. (Computational mathematics and mathematical physics, 2024)
The generation of high-quality computational mesh plays an important role in high-accuracy computation of supersonic flows over bodies. Priority is given to mesh adaptation to discontinuities, primarily, to bow shocks. In this paper, a mesh is treated as a mechanical system with elastic connections and an algorithm for mesh adaptation to a flow field with a bow shock is considered. The application of the algorithm to a typical structured mesh leads to mesh refinement in high field gradient regions achieved by drawing mesh lines into the shock vicinity, while maintaining the quality of the mesh elements. The problems considered demonstrate the possibility of applying the described algorithm to realistic flow problems of practical interest.